Divine Diction: Heavenly Speech among Sethians, Valentinians, and Ignatius - Abbott, Philip (Harvard theological review, 2025)
While ancient people defined themselves largely by their ability to employ correct speech in Greek or Latin, many early Christians discussed a foreign type of speech from heaven. This celestial communication medium created a different criterion to establish status and identity in Christian communities. This article explores conceptions of this heavenly speech in Sethian and Valentinian writings, as well as in Ignatius. Sethians and Valentinians appeal to different sensory perceptions to describe celestial communication. For Sethians, heavenly speech is imbued with light and is conceptualized through visual frameworks, whereas for Valentinians, celestial communication functions like smell. In contrast, Ignatius associates celestial speech with a person: the bishop. That is, Ignatius defines celestial communication as whatever the bishop communicates, whether spoken or silent. For all these second- and third-century Christians, correct employment of celestial speech forges a unique social structure and reifies boundaries for a given in-group.